Recruitment, effort, and retention effects of performance contracts for civil servants: experimental evidence from Rwandan primary schools - Leaver, C; Ozier, O; Serneels, P; Zetlin, A (American Economic Association, 2021)
This paper reports on a two-tiered experiment designed to separately identify the selection and effort margins of pay-forperformance (P4P). At the recruitment stage, teacher labor markets were randomly assigned to a ‘pay-for-percentile’ or fixed-wage contract. Once recruits were placed, an unexpected, incentivecompatible, school-level re-randomization was performed, so that some teachers who applied for a fixed-wage contract ended up being paid by P4P, and vice versa. By the second year of the study, the within-year effort effect of P4P was 0.16 standard deviations of pupil learning, with the total effect rising to 0.20 standard deviations after allowing for selection.